Identification of a Novel NOG Missense Mutation in a Chinese Family With Symphalangism and Tarsal Coalitions - Xiong, Jing; Tu, Wei; Yan, Yifei; Xiao, Kai; Yao, Yanyi; Li, Shouxin; Yang, Liu; Zhou, Min; Liu, Yang; Hu, Jin; Zhu, Feng (Frontiers in Genetics, 2019)
Background: Proximal symphalangism (SYM1) is a rare genetic bone disorder characterized by the fusion of proximal interphalangeal joints in the hands and feet. Genetic studies have identified two genes underlying SYM1 as the noggin (NOG) and the growth differentiation factor 5 (GDF5). Case report: In the present report, a 43-year-old gravida at 11 weeks of gestation was referred for evaluation of abnormal fusions of the joints. In the initial diagnosis, physical examination was undertaken. However, traditional radiological examination was not applied due to the need to protect the fetus, making diagnosis results inefficient to determine the exact disease affecting the proband. To acquire alternative clinical evidences, we conducted radiological examinations on two other affected family members. The radiological examination revealed that they carried the symphalangism accompanied with tarsal coalition, a very rare manifestation of SYM1. A combination of whole exome sequencing (WES) and Sanger sequencing revealed a novel heterozygous missense mutation (c.163G>T; p.Asp55Tyr) in the NOG gene, which could be associated with the observed pathogenic SYM1 in the studied family. The p.Asp55Tyr mutation co-segregated with SYM1 through the affected and unaffected family members. In silico structural modeling of the p.Asp55Tyr mutation showed that it abolishes the interaction with the Arg167 residue and causes a change in the electrostatic potential profile of the type II binding site of the noggin protein. Conclusion: Our findings indicate that the genetic test based on WES can be useful in diagnosing SYM1 patients, with particular advantages in preventing the fetus from contacting harmful X-ray through the traditional radiography. The novel pathogenic mutation identified would further expand our understanding of the mutation spectrum of NOG in association with SYM1 disease and provide a guidance on how to determine whether the fetus is affected by SYM1 through the prenatal diagnosis.